Hubungan Tingkat Pengetahuan Kontrasepsi Kondom pada Pasangan Usia Subur (PUS) - Baso, Vilsha Ola Lolo; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2026)
Family Planning (FP) is one of the government's strategic programs aimed at improving family welfare through birth control and reproductive health enhancement. Couples of reproductive age are the primary target of this program because they have a high probability of pregnancy. However, the use of condom contraception remains relatively low compared to other contraceptive methods. Knowledge is considered one of the factors influencing an individual's behavior in selecting contraceptive methods. This study aimed to determine the effect of educational intervention on knowledge levels and condom contraceptive use among couples of reproductive age. This study employed a quantitative pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 32 respondents selected using purposive sampling techniques. Data were collected through structured questionnaires and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The findings showed a significant difference in knowledge levels before and after intervention (p=0.000), as well as a significant difference in condom contraceptive use before and after intervention (p=0.000). The study indicates that educational intervention effectively improved knowledge and increased condom contraceptive use among couples of reproductive age. These findings suggest that health education programs may contribute to improving reproductive health behavior within the community.